2021
DOI: 10.3390/foods10020460
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Antioxidant Potential of Fiddleheads from European Ferns

Abstract: Ferns are part of the diet and traditional medicine in East Asia, North America, and Oceania, however, their importance has been forgotten in Europe. Here, the nutritional and antioxidant potential of young fern fronds (fiddleheads) of eight families were studied. Most of the tested fern species excelled in high antioxidant capacity when compared to the reference leafy vegetables spinach and rocket. On average, the total phenol content reached 220 mg·g−1 of extract dry weight for all fiddleheads, and 15 out of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 53 publications
0
14
1
1
Order By: Relevance
“…The β-carotene content was 36.31 ± 3.41 mg/100 g D.W., which is consistent with the findings of [49], who reported a β-carotene content of 36.00 ± 0.01 mg/100 g in dried rocket leaves. However, both β-carotene and lutein contents found in this study were higher than the values reported by previous studies [46][47][48]. Figure 6 shows the effect of PAW treatment on the carotenoid content of control and treated samples.…”
Section: β-Carotene and Lutein Contentscontrasting
confidence: 80%
See 2 more Smart Citations
“…The β-carotene content was 36.31 ± 3.41 mg/100 g D.W., which is consistent with the findings of [49], who reported a β-carotene content of 36.00 ± 0.01 mg/100 g in dried rocket leaves. However, both β-carotene and lutein contents found in this study were higher than the values reported by previous studies [46][47][48]. Figure 6 shows the effect of PAW treatment on the carotenoid content of control and treated samples.…”
Section: β-Carotene and Lutein Contentscontrasting
confidence: 80%
“…Long-chain carotenoids are significantly more susceptible to oxidation and isomerization, which can happen during processing and storage [45]. Lutein and β-carotene have been reported to be the most abundant carotenoids in rocket leaves [46][47][48][49]. A higher content of β-carotene than that of lutein in both garden and wild rocket samples has been previously reported [46], however, lutein was reported at higher concentrations in rocket leaves [47,48].…”
Section: β-Carotene and Lutein Contentsmentioning
confidence: 97%
See 1 more Smart Citation
“…1 µg AsA/g FW (or ~5 µg of total AsA/g FW, [ 16 ]) while common species of the genus Polypodium or Dryopteris contained ca. 300–1300 µg AsA/g FW [ 25 ], indicating that the AsA quantification in ferns requires further analytical investigation. In line with the more negative impact of Cd on the ROS balance (i.e., enhanced ROS formation), the amount of AsA decreased in the leaves ( Figure 3 ), although no visible signs of damage were observed.…”
Section: Resultsmentioning
confidence: 99%
“…In certain Eastern cultures of the European continent fronds of ferns are used as a food source ( Langhansova et al, 2021 ). The young fronds of ferns (named fiddleheads), which generally exhibit a higher total phenol content than the corresponding mature fronds, are a source of nutrients and phytochemicals with a high potential to reduce oxidative stress of diseases associated with ageing ( Dvorakova et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%